Pengaruh Diet Beras Hitam, Kacang Merah dan Daun Kelor (Betamelor) Terhadap Perubahan Berat Badan Tikus Sprague-Dawley - Lina Yunita; Herianus Lalel; Stefanus Manongga (Kupang Journal of Food and Nutrition Research, 2020)
This study aims to analyze the effect of black rice, red beans and Moringa (betamelor) leaves on the body weight of Sprague-Dawley rats. This study is an experimental study in experimental animals, using factorial group design with a post test only control group. The research sample was 25 female Sprague-Dawley mice aged six months, grouped into one control group (K) and three treatment groups (P) with 80% (P1), 50% (P2) and 20% (P3) in the diet given. The intervention was carried out for 28 days. Weight was weighed every week while consumption measurements were taken every day. Standard feeding of BR II 5% of body weight per day made the weight of the control group rats (without betamelor) increase 21.7% after 28 days of intervention, higher than the P1, P2, and P3 groups, each of which gained weight 14.9%, 17.6% and 20.3%. After 28 days of intervention, there is significant differences between groups (p> 0.05).